(untitled) (Nigerian Journal of Physiological Sciences, 2020)
Gaseous emission, particulate emission, biological molecules and other harmful substances discharge into the atmosphere from dumpsite environment. The carbon dioxide (CO2) and methane (CH4) content of the gaseous emission from different platforms and offsets of the Awotan dump site were measured. P Sense CO2 Meter AZ 7755 was used to measure the level of carbon dioxide gas, temperature and relative humidity. K60 Gas detector was used to measure the level of methane (CH4) gas and Pm 2.5. Thermo-scientific MIE pDR 1500 PM monitor was used to measure the particulate matter on the dumpsite. The CO2 levels (697±28.84 - 502±2.19) were above the minimum permissible levels of ASHRAE of 400ppm for all platforms at the dumpsite. CH4 levels range (73.33±3.32 – 18.33±4.27) was above the methane explosive limits (MEL) of 15% for all Platforms, however the level at 25m and 50m offsets (14.83±4.11 – 13.83±2.48) was below the MEL for 75m and 100m offsets. PM2.5 levels were lower in the morning and peaked in the afternoon at Platform 5, 6 and 9 locations with values of 62.76±6.03, 63.9±11.37 and 32.06±3.89 respectively which is not within the WHO minimum permissible limit of 25µg/m3. There was a significant positive correlation between CO2 and CH4 (r=0.7558, p=0.028) but no significant correlation between CO2 and other meteorological parameters (temperature and humidity) (r=-0.1309, p=0.67and r=0.09644, p=0.754). The carbon dioxide and methane content of the gaseous emission from the Awotan dump site are potential health hazard, hence the need for an engineering design that will reduce the quantum of the emission thereby reducing the hazard.